2009
DOI: 10.1021/cc9001313
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonic Acid Functionalized Ionic Liquid in Combinatorial Approach, a Recyclable and Water Tolerant-Acidic Catalyst for One-Pot Friedlander Quinoline Synthesis

Abstract: SO(3)H-functionalized ionic liquid was successfully applied as a water tolerant-acidic catalyst for the one-pot domino approach quinoline synthesis in aqueous medium. Various types of quinolines from 2-aminoaryl ketones and beta-ketoesters/ketones were prepared in 85-98% yields using the catalytic system of SO(3)H-functionalized ionic liquid/H(2)O. The ionic liquids was synthesized in a combinatorial fashion. The quinoline products could be conveniently separated from the reaction mixture by filtration, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…These compounds are important for the synthesis of ne chemicals and other industrial applications and have great potential for development [5][6][7]. The crystal structures of some similar 1,3-dioxanes have been reported [8][9][10][11]. The bond lengths and angles are in the expected ranges.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are important for the synthesis of ne chemicals and other industrial applications and have great potential for development [5][6][7]. The crystal structures of some similar 1,3-dioxanes have been reported [8][9][10][11]. The bond lengths and angles are in the expected ranges.…”
Section: Discussionmentioning
confidence: 99%
“…The crude yellow products were washed with water and purified by 41.1, 50.6, 89.0, 109.7, 119.2, 127.1, 127.5, 128.6, 144.4, 144.7, 148.4, 195.4. IR (KBr): m 3,288, 3,072, 2,962, 2,930, 2,885, 2,811, 2,751, 2,204, 1,659, 1,608, 1,490, 1,469, 1,382, 1,341, 1,319, 1,260, 1,148 m 3,306, 3,226, 3,096, 2,960, 2,880, 2,811, 2,197, 1,657, 1,638, 1,496, 1,434, 1,394, 1,365, 1,316, 1,258, 1,198, 1,166, 1,144, 1,129, 1,067, 1,010 1,660, 1,607, 1,491, 1,470, 1,435, 1,381, 1,316, 1,258, 1,147, 1,020 1,657, 1,609, 1,499, 1,460, 1,434, 1,382, 1,316, 1,257, 1,163, 1,147, 1,138, 1,100, 1 13 1,658, 1,604, 1,501, 1,470, 1,435, 1,381, 1,316, 1,259, 1,148, 1,131, 1,100, 1,045 …”
Section: Methodsmentioning
confidence: 99%
“…The United States government-sponsored clinical trials for antimalarial drug development showed unequivocally that chloroquine has a significant therapeutic value as an antimalarial drug. Accordingly, novel strategies for the synthesis of quinolines continued to receive considerable attention in the field of organic synthetics chemistry [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]. The easy and efficient route for the synthesis of 1,2,4,5-tetrazines can be done by the addition of hydrazine to aromatic cyanide or aromatic nitriles followed by the oxidation of the 1,2-dihydrotetrazine product [7,8]. Although, this methodology has some demerits like it does not work for producing tetrazines from unactivated nitriles means with alkyl nitriles [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%